Focusing on rare diseases in China: are we there yet?. Issue 1 (December 2015) - Yang, Li; Su, Chang; Lee, Ashley; Bai, Harrison
Abstract The Chinese researchers have made significant progress in studying rare diseases in the recent years. From 2000 to 2014, 269 out of 1892 clinically relevant original research papers published on high impact journals by Chinese institutions, and 2678 out of 6040 clinical trials conducted by Chinese institutions and registered at ClinicalTrial.gov are focused on rare diseases. The number of research papers and of clinical trials has shown a steady trend of increase. Creating public databases for rare disease will escalate progress in rare disease and enable multicenter studies.